2011
DOI: 10.1159/000329450
|View full text |Cite
|
Sign up to set email alerts
|

The Correlates and Treatment of Obesity in Military Populations: A Systematic Review

Abstract: Objective: The emergence of obesity as a distinct disease could have far reaching consequences for an organisation where optimum health and physical fitness are required for personnel to perform their occupational roles effectively. The objectives of this paper are to systematically review the literature concerning correlates and treatment of obesity in military populations. Methods: Through computerised searches of English language studies, 17 papers were identified (treatment (13), correlates (4)). Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 55 publications
2
42
0
Order By: Relevance
“…Two studies on military populations have reported elevated levels of obesity in the soldier populations as opposed to the officer populations (Bray et al, 2009;Mullie et al, 2008). One recent study indicated that a correlation might exist between the hierarchical system of rank employed within the military and 'pay-group', with higher rank commanding higher pay (Sanderson et al, 2011). This would suggest that rank within the military is a proxy for socioeconomic (SES) status.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies on military populations have reported elevated levels of obesity in the soldier populations as opposed to the officer populations (Bray et al, 2009;Mullie et al, 2008). One recent study indicated that a correlation might exist between the hierarchical system of rank employed within the military and 'pay-group', with higher rank commanding higher pay (Sanderson et al, 2011). This would suggest that rank within the military is a proxy for socioeconomic (SES) status.…”
Section: Discussionmentioning
confidence: 99%
“…Research in 2007 estimated that spending on medical care associated with weight and obesity for the entire U.S. department of defense was in excess of $1.1 billion [19]. To combat these rising costs, research has investigated methods of prevention and found that a multi-component approach to obesity in the military is cost effective [20]. This type of research has included implementing intervention programs in several populations.…”
Section: Body Compositionmentioning
confidence: 99%
“…These programs include LEAN [2124], lifestyle change, individual readiness, fitness excellence and eating healthy (LIFE) [25] and fat loss and exercise (FLEX) [26]. Research that evaluated these programs found that they were developed for a U.S. population and may not be suitable for other military populations [20]. …”
Section: Body Compositionmentioning
confidence: 99%
“…Still, overweight and obesity are increasing in armed forces as in civilian populations [2]. Among Finnish conscripts, average body weight has increased in 15 years from 71 to 77 kg while height has remained constant [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Soldiers are offered regular nutritionally-planned main meals [11] in a structured environment which offers a good setting for intervening. To our knowledge there have been only a few interventions targeting eating habits and obesity in military populations [2]. A central topic in the existing interventions has been supporting lifestyle or behavioral change also through a supportive environment [18-22].…”
Section: Introductionmentioning
confidence: 99%